The Impact of Indonesia’s Economic and Political Policy Regarding Participation in Various International Forums: G20 Forum (Literature Review of Financial Management) - Farhan Saputra; Hapzi Ali (DINASTI RESEARCH, 2021)
Indonesia is one of the countries with great economic power. Even in ASEAN countries, Indonesia is the first ranked as the country with the most robust. Even in Asia, Indonesia is ranked fifth as the most robust economy after China, Japan, India, and South Korea. It makes Indonesia be not able to underestimate. With high economic growth, Indonesia is trusted by the International World as the host in various events. Namely as the 2022 G20 Forum host, the IMF and World Bank Group activities in Bali in 2018. This certainly positively impacts Indonesia, both in the political and economic fields, which will later lead to confidence in foreign investors to invest their capital in Indonesia, which will also impact the opening of job opportunities. This article reviews the impact of Indonesia's Economic and Political Policies regarding participation in various International Forums: the G20 Forum. Which is a form of qualitative research and literature or library research, a study of Financial Management literature. The results of this literature review article are: 1) The G20 Forum has an effect on the Indonesian Economy; 2) The G20 Forum has an effect on the Political Policy; 3) the Political Policy has and effect on the Indonesian Economy